Analysis of Leverage, Managerial Ownership, and Dividend Policy in Agency Theory Perspective - Tjong, William; Stevanie, Stevanie (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2023)
The purpose of this research is to test the effect of leverage, managerial ownership, and dividend policy on agency conflict. The agency conflict in this study is proxied by the value of the company measured through Tobin's Q Ratio, while the independent variables use leverage, managerial ownership, and dividend policy. The partial analysis tools in this study used Ordinary Less Square (OLS). Samples are companies listed on Indonesia Stock Exchange for the period of study. The results of this study are leverage has a negative relationship in reducing agency conflict in companies, managerial ownership does not affect the firm value, and dividend policy has a positive and significant effect in reducing agency conflict in companies.